Impact and consequences of the consumption of ultra-processed foods on children's health (Research, Society and Development, 2022)
The objective of this work was to carry out a cross-sectional study of the literature on the association between the consumption of ultra-processed foods and their consequences on children's health. The searches were carried out in the Scielo, PubMed, Lilacs and Repositories databases. Articles that evaluated the consequences of the consumption of ultra-processed foods and the outcomes on child health were selected. The review process resulted in the selection of 20 studies published in the last 10 years. Ultra-processed foods (UPF) are industrial formulations typically made with five or more ingredients, including food substances and additives. Adequate nutrition in childhood, especially up to two years of age, is a phase of extreme importance for the promotion of health, growth, development and formation of children's eating habits. However, dietary practices in childhood have not occurred as recommended and the introduction of ultra-processed foods in the children's diet is increasingly early. Therefore, it can be concluded from this review that the consumption of ultra-processed foods is associated with several non-communicable chronic diseases and their risk factors, which can have important implications for child health.